2012
DOI: 10.1017/s0956536112000156
|View full text |Cite
|
Sign up to set email alerts
|

Tikal's Early Classic Domination of the Great Western Trade Route: Ceramic, Lithic, and Iconographic Evidence

Abstract: This article reviews new evidence suggesting that Tikal and its allies controlled trade along the Pasión River during the latter half of the Early Classic period (ca.a.d.460–550) and the possible impacts this had on geopolitical interaction. Recent data in the Candelaria Caves and other Pasión River sites showed the strong influence of Tikal during this time period that could indicate that they were active agents in interregional trade between the Maya highlands and lowlands. A quantitative reevaluation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Our research identified Junco 4 occupation dating to this assumed period of abandonment, which indicates that there was some continuity in the population of Ceibal, albeit diminished, from the Junco phase to the Late Classic Tepejilote phase. Tikal's influence over the Pasión region appears to have ceased after its defeat in AD 562 (41), but the Ceibal dynasty may have persisted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research identified Junco 4 occupation dating to this assumed period of abandonment, which indicates that there was some continuity in the population of Ceibal, albeit diminished, from the Junco phase to the Late Classic Tepejilote phase. Tikal's influence over the Pasión region appears to have ceased after its defeat in AD 562 (41), but the Ceibal dynasty may have persisted.…”
Section: Resultsmentioning
confidence: 99%
“…Centers in the peripheral zones of the Maya lowlands likely had some forms of political centralization during the Preclassic Period, but the historically known dynasties of these regions, such as Ceibal, Yaxchilan, Piedras Negras, Palenque, and Copan, appear to have originated during the fourth and fifth centuries, in some cases through connections with the developed dynasties of the central lowlands. Tikal, in particular, appears to have spread its political influence to Ceibal and other parts of the Pasión region, whose population levels continued to be low in the wake of the Preclassic collapse (41).…”
Section: Discussionmentioning
confidence: 99%
“…Note that many other recent publications, cited for various specific interpretations, deal more directly and in detail with the specific evidence on aspects of Cancuen including the most recent analyses of the obsidian assemblage (Andrieu, Quiñonez, and Rodas 2011;Andrieu et al , 2012, ceramics and chronology , 2013Forné and Torres 2010Torres et al 2013), ideological systems legitimating economic power ( Barrientos 2008Barrientos , 2014 Barrientos and ; the extent of the site and its sustaining area Demarest et al 2009Demarest et al , 2013Wolf and Bracken 2013a), epigraphy and political relations (Barrientos 2014;Fahsen and Barrientos 2006;Fahsen and Jackson 2001;Jackson 2004Jackson , 2005, new understandings of Cancuen's role in nonexotic, basic commodity production and exchange (Demarest and Martínez 2013;Demarest et al 2013), corrected and new analyses of jade working (Andrieu et al , 2012Andrieu, Quiñonez and Rodas 2011), the significance of local ceramic types and imports , and instrumental neutron activation analysis (INAA) of both Torres et al 2013), cave ritual (Spenard 2006;Woodfill 2010;Woodfill and Andrieu 2012), frontier relations (Demarest and Martínez 2013;Demarest et al 2013;Wolf and Bracken 2013b), and evidence on Cancuen's violent collapse Demarest et al 2014;Quintanilla and Demarest 2013;Suasnávar et al 2007;Winburn et al 2013. Note that many other recent publications, cited for various specific interpretations, deal more directly and in detail with the specific evidence on aspects of Cancuen including the most recent analyses of the obsidian assemblage (Andrieu, Quiñonez, and Rodas 2011;Andrieu et al , 2012, ceramics and chronology …”
mentioning
confidence: 99%
“…The "Greater Cancuen" area extends for several kilometers beyond the epicenter peninsula, depending on direction (Demarest and Martínez 2013;Demarest et al 2013). Cave shrines 8 to 12 km from the epicenter have been excavated and there the very characteristic Cancuen ceramic assemblage ends Spenard 2006;Torres et al 2013;Woodfill 2010). Cave shrines 8 to 12 km from the epicenter have been excavated and there the very characteristic Cancuen ceramic assemblage ends Spenard 2006;Torres et al 2013;Woodfill 2010).…”
mentioning
confidence: 99%
“…given the presence of Tikal-style material culture at sites along the great Western Trade Route to the El Chayal obsidian source in the guatemalan highlands (Woodfill and Andrieu 2012), Tikal should have lots of obsidian in the Early Classic. It certainly does.…”
Section: Chunchucmil As a Gateway Centermentioning
confidence: 99%